Clinical application of catheter-based renal sympathetic denervation for the treatment of resistant hypertension - TANG Xiao-tie; ZHOU Tao (Linchuang shenzangbing zazhi)
Objective To investigate the safety and efficacy of catheter-based renal sympathetic denervation（RSD） in the treatment of resistant hypertension.Methods Thirty-two patients with resistant hypertension were treated with RSD and followed up for 12 months.Blood pressure,renal function and total dosages of antihypertensive medications were recorded respectively and compared hefore and after the procedure at 3rd,6th and 12 th month.CT scan was scheduled to observe renal artery during the follow-up period Results At 3rd month after RSD,the systolic and diastolic blood pressure was（18.5 ± 3.6） mm Hg（P<0.01） and（5.8 ± 2.5） mm Hg（P<0.01） respectively,significantly lowef than that of the procedure before RSD.Similarly,the systolic and diastolic blood pressure at 6th month after RSD was（24.3 ± 2.2） mm Hg（P<0.01） and（8.7 ± 2.6） mm Hg（P<0.01）,which was decreased as compared with that before RSD respectively;Furthermore,at 12 th month after RSD the systolic and diastolic blood pressure was（20.7 ± 3.2） mm Hg（P<0.01） and（6.6 1.8） mm Hg（P<0.01）,which was decreased as compared with that before RSD respectively.There no severe hypotension and complications.During the follow-up period of 3,6 and 12 months,the categories of antihypertensive medications used were significantly reduced by 43.7%（P<0.01）,41.9%（P<0.01） and 44.8%（P<0.01） respectively as compared with those before RSD.The eGFR,creatinine and cystatin levels showed no significant change before and 3,6,12 months after RSD（P>0.05）.At 3rd,6th,and 12 th month after RSD,the heart rate was significantly decreased as compared with that before RND（P<0.05）.No abnormality of renal artery and renal function was observed after the procedure of RND.Conclusions RSD is a relatively simple,safe and effective interventional therapy to treat resistant hypertension.It deserves promotion in clinical practice.